Impact of preanalytical conditions on plasma concentration and size distribution of extracellular vesicles using Nanoparticle Tracking Analysis. Issue 1 (December 2018) - Jamaly, Simin; Ramberg, Cathrine; Olsen, Randi; Latysheva, Nadezhda; Webster, Paul; Sovershaev, Timofey; Brækkan, Sigrid; Hansen, John-Bjarne
Abstract Optimal pre-analytical handling is essential for valid measurements of plasma concentration and size distribution of extracellular vesicles (EVs). We investigated the impact of plasma preparation, various anticoagulants (Citrate, EDTA, CTAD, Heparin), and fasting status on concentration and size distribution of EVs measured by Nanoparticle Tracking Analysis (NTA). Blood was drawn from 10 healthy volunteers to investigate the impact of plasma preparation and anticoagulants, and from 40 individuals from a population-based study to investigate the impact of postprandial lipidemia. Plasma concentration of EVs was measured by NTA after isolation by high-speed centrifugation, and size distribution of EVs was determined using NTA and scanning electron microscopy (SEM). Plasma concentrations and size distributions of EVs were essentially similar for the various anticoagulants. Transmission electron microscopy (TEM) confirmed the presence of EVs. TEM and SEM-analyses showed that the EVs retained spherical morphology after high-speed centrifugation. Plasma EVs were not changed in postprandial lipidemia, but the mean sizes of VLDL particles were increased and interfered with EV measurements (explained 66% of the variation in EVs-concentration in the postprandial phase). Optimization of procedures for separating VLDL particles and EVs is therefore needed before NTA-assessment of EVs can be used as biomarkers of disease.